Peningkatan Kelarutan Ketoprofen Dalam Bentuk Mikropartikel Dengan Metode Emulsification-Ionic-Gelation Menggunakan Polyvinylprrolidone (PVP) Dan Tripolifosfat(TPP) - Dirgahayu Yahya, Nurul Fitri; Sinala, Santi; Stevani, Hendra (Media Farmasi, 2024)
A nonsteroidal anti-inflammatory drug called ketoprofen is used to treat musculoskeletal and joint disorders, including osteoarthritis. Ketoprofen has a low solubility in water, which is a major obstacle to the absorption of the drug into the body.However, by using emulsification ion gelation technology, it is possible to create microparticles, which can improve the solubility of ketoprofen. . The aim of this study was to use emulsification and ion gelation to produce ketoprofen microparticles with higher solubility. SEM was used to characterize the structure of the ketoprofen particles. Subsequently, ketoprofen solubility and content tests were performed. When the properties were evaluated using SEM microparticles, the particle size gradually decreased from pH2, pH4, and pH6, and the water solubility of the drug increased due to the small particle size of the generated microparticles. After the emulsification-ionic gelation process, the solubility of ketoprofen increased two-fold and the pH of water increased two-fold compared to untreated ketoprofen. From this, it can be concluded that polyvinylpyrrolidone (PVP) and tripolyphosphoric acid (TPP) effectively improved the solubility of sparingly water-soluble ketoprofen in the emulsification ion gelation process of ketoprofen production.